Estudo Exploratório Sobre o Uso da Arquitetura de Microsserviços na Indústria de Software - Deprá, Tamires G. B. (2021)
The microservice architecture, although very recent, already shows great impact in the software industry. Most varied companies’ size and segments adopted this architectural style. However, a small number of scientific papers present discussion about the adoption of microservice architecture in the software industry. In this work, we tried to identify if the software companies use the microservices architecture and how they use it. For this purpose, an evaluation questionnaire was applied to a set of software development companies in the city of Maringá - PR. We invited to participated of this research 35 companies, of that total, 23 companies accepted. Considering the data resulting from the questionnaire application, it was possible to observe that a significant number of companies use the microservice architecture (39.1 %). In addition, it was observed that good practices for the development of microservices discussed in the literature are adopted by the companies participating in the study.